Improved dislocation density-based models for describing hot deformation behaviors of a Ni-based superalloy. Issue 16 (14th June 2016) - Lin, Y.C.; Wen, Dong-Xu; Chen, Ming-Song; Liu, Yan-Xing; Chen, Xiao-Min; Ma, Xiang
Abstract: Abstract : Generally, the obvious work hardening, dynamic recrystallization (DRX), and dynamic recovery behaviors can be found during hot deformation of Ni-based superalloys. In the present study, the classical dislocation density theory is improved by introducing a new dislocation annihilation item to represent the influences of DRX on dislocation density evolution for a Ni-based superalloy. Based on the improved dislocation density theory, the peak strain corresponding to peak stress and the critical strain for initiating DRX can be determined, and the improved DRX kinetics equations and grain size evolution models are developed. The physical framework and algorithmic idea of the improved dislocation density theory are clarified. Moreover, the deformed microstructures are characterized and quantitatively correlated to validate the improved dislocation density theory. It is found that the improved dislocation density-based models can precisely characterize hot deformation and DRX behaviors for the studied superalloy under the tested conditions.